Correlation of serum lipids and glycosylated hemoglobin with cognitive function in peritoneal dialysis patients - Mai Zhang; Hua-ying Pei (Editorial Department of Journal of Clinical Nephrology, 2024)
Objective To explore the relevant factors affecting cognitive function in continuous ambulatory peritoneal dialysis (CAPD) patients and evaluate the relationship between blood lipids and glycosylated hemoglobin and cognitive function in CAPD patients. Methods From January 2021 to December 2022, the relevant clinical data were reviewed for 312 clinically stable patients on a regular dialysis for more than 3 months. Overall cognitive function was evaluated by Montreal Cognitive Assessment (MoCA). Trail-Making test A was utilized for evaluating executive functions. Also the relationship was examined between factors such as lipids and glycated hemoglobin and cognitive functions. Results The incidence of cognitive impairment in CAPD patients at peritoneal dialysis center of our hospital was 36.9%. Age [(56.99±9.80) years vs (44.93±11.64) years], glycated hemoglobin [5.5(5.2, 6.08)% vs 5.1(4.8, 5.6)%], serum potassium [4.2(3.9, 4.6）mmol/L vs 4.1 (3.8, 4.4）mmol/L] and low-density lipoprotein cholesterol (HDL-C) [2.55(2.13, 3.04) mmol/L vs 2.43 (2.01, 2.70) mmol/L] were higher in cognitive impairment group than those in non-cognitive impairment group. Education level, total iron binding capacity [50.4(45.0, 55.6) μmol/L vs 52.4(47.2, 59.1) μmol/L] and serum level of albumin [(36.0±3.9) g/L vs (37.1±3.8) g/L] were lower in cognitive impairment group ( P < 0.05). Serum albumin and education level were correlated positively with MoCA score ( r = 0.126, P = 0.025; r = 0.216, P < 0.001). Age and glycated hemoglobin were negatively correlated with MoCA score ( r = -0.547, P < 0.001; r = -0.264, P < 0.001). Age was correlated positively with TMT-A time ( r = 0.126, P < 0.001) while serum sodium and education level were correlated negatively with TMT-A time ( r = −0.157, P = 0.046; r = −0.244, P = 0.002). No correlation existed between lipids, MoCA score and TMT-A time ( P > 0.05). Further analysis revealed a significant difference in HDL-C between two groups ( P < 0.05) while correlation analysis indicated that HDL-C was not correlated with CI ( r = 0.156, P > 0.05). Age, education level, serum albumin and HbA1c were the influencing factors of cognitive function. Serum albumin was a protective factor of cognitive function ( OR = 0.978, 95% CI: 0.917-1.040). Age, education level and HbA1c ( OR = 1.203, 95% CI: 1.176-1.230; OR = 5.565, 95% CI: 1.962-15.789; OR = 1.694, 95% CI: 1.348-2.040) were risk factors for cognitive function. Receiver operating characteristic (ROC) curves of HbA1c and serum albumin showed an area under the curve (AUC) of 0.651 (95% CI: 0.570-0.732) and 0.583 (95% CI: 0.518-0.648) with predictive values for cognitive impairment. Jordon index was the largest (0.315) when HbA1c definition value was 5.15%. At a defined value of serum albumin 35.6 g/L, Jordon index was the largest (0.149). Conclusions For CAPD patients, blood lipid is not a risk factor for cognitive function. Glycated hemoglobin A1c is a risk factor for cognitive function so that monitoring and controlling its level may lower the risk of cognitive impairment in CAPD patients.